Improved dementia screening for elderly with low education in South Korea using the Cognitive Impairment Screening Test (CIST) - Kang, Kyung Wook; Park, Gilsoon; Kim, Hyunsoo; Cho, Soo Hyun; Choi, Seong-Min; Choi, Kang-Ho; Lee, Hak-Loh; Shon, Gwangsoon; Kim, Byeong C.; Kim, Hosung (Frontiers in Neuroscience, 2025)
BackgroundThe Mini-Mental State Examination (MMSE) is the most widely used cognitive screening test worldwide; however, it often overdiagnoses older adults with low education levels. In contrast, the Cognitive Impairment Screening Test (CIST), developed by South Korea’s Ministry of Health and Welfare, may address this shortcoming. In this study, we compare the CIST and the Korean version of the MMSE (K-MMSE) in older adults with no formal education.MethodsWe included 100 older adults (≥ 65 years)—27 with normal cognition (NC), 37 with mild cognitive impairment (MCI), and 36 with dementia (DM). All completed both the CIST and K-MMSE. First, we analyzed correlations between the CIST and K-MMSE. Next, we performed an analysis of covariance (ANCOVA), adjusting for age and sex, to compare group performance. Finally, classification performance was evaluated using receiver operating characteristic (ROC) curve analyses, examining the area under the curve (AUC) and other relevant metrics.ResultsThe CIST showed positive correlations with both the K-MMSE (r = 0.722) and the K-MMSE z-score (r = 0.625). ANCOVA revealed significant group differences (p < 0.001) for both measures. When distinguishing NC from MCI/DM, the CIST outperformed the K-MMSE, demonstrating a higher AUC (0.869 vs. 0.842) and F1-score (0.697 vs. 0.409).ConclusionThe CIST is a reliable and useful tool for assessing cognitive function, showing advantages over the K-MMSE in detecting cognitive decline among older adults without formal education. Further large-scale validation studies are warranted.